Investigation of Molybdenite Concentrate Roasting in Chamber and Rotary Furnaces - Kan, Selçuk; Benzeşik, Kağan; Odabaş, Ömür Can; Yücel, Onuralp (Springer Science and Business Media LLC, 2021)
Extraction and processing constitute an important area in the metallurgy of molybdenum. Molybdenum trioxide (MoO3) production is one of the most important stages in molybdenum production. In this study, the effects of different furnace types on MoO3 production were investigated by using molybdenum concentrate as a raw material obtained during the enrichment of copper ores. Preliminary experiments have been made using a chamber type furnace, and a transition to a pilot-scale has been carried out with rotary kiln experiments. The effects of a different time and atmospheric conditions on MoO3 roasting kinetics were investigated by experimental studies conducted in the temperature range of 500–650°C. It was determined that the optimum temperature and time for sulfur (S) removal was 625°C and 180 min in the studies carried out in the rotary kiln, and it was determined that 0.61% S content was reached with an average removal efficiency of 98%. The activation energy in these sets was calculated as 89.519 kJ/mol.